Baicalin: a potential therapeutic agent for acute kidney injury and renal fibrosis - Li, Xiaoming; Xu, Rui; Zhang, Dan; Cai, Ji; Zhou, He; Song, Tao; Wang, Xianyao; Kong, Qinghong; Li, Liujin; Liu, Zhaohui; He, Zhixu; Tang, Zhengzhen; et al. (Frontiers in Pharmacology, 2025)
Acute kidney injury (AKI) is a common critical clinical disease that is linked to significant morbidity, recurrence, and mortality. It is characterized by a fast and prolonged loss in renal function arising from numerous etiologies and pathogenic pathways. Renal fibrosis, defined as the excessive accumulation of collagen and proliferation of fibroblasts within renal tissues, contributes to the structural damage and functional decline of the kidneys, playing a pivotal role in the advancement of Chronic Kidney Disease (CKD). Until now, while continuous renal replacement therapy (CRRT) has been utilized in the management of severe AKI, there remains a dearth of effective targeted therapies for AKI stemming from diverse etiologies. Similarly, the identification of specific biomarkers and pharmacological targets for the treatment of renal fibrosis remains a challenge. Baicalin, a naturally occurring compound classified within the flavonoid group and commonly found in the Chinese herb Scutellaria baicalensis, has shown a range of pharmacological characteristics, such as antioxidant, anti-inflammatory, antifibrotic, antitumor and antiviral effects, as evidenced by research studies. Research shows that Baicalin has potential in treating kidney diseases like AKI and renal fibrosis. This review aims to summarize Baicalin’s progress in these areas, including its molecular mechanism, application in treatment, and absorption, distribution, metabolism, and excretion. Baicalin’s therapeutic effects are achieved through various pathways, including antioxidant, anti-inflammatory, antifibrosis, and regulation of apoptosis and cell proliferation. Besides, we also hope this review may give some enlightenment for treating AKI and renal fibrosis in clinical practice.